Six sigma for value creation: an interventionist approach / Lukman Ibrahim - Ibrahim, Lukman (Institute of Graduate Studies, UiTM, 2014)
The literature of Six Sigma mainly concerns with its underlying concepts and success stories written by consultants or people with vested interests, which raises questions about their validity. Hence, there is a genuine need to conduct a study to investigate the extent to which Six Sigma influences organizational performance and to document the details of Six Sigma implementation empirically. As with other innovations that diffuse through time, this study of Six Sigma implementation in a Malaysian automotive company was carried out using a longitudinal case study method in order to investigate the reasons for adopting it, how it was implemented and what the consequences were for the company. This interventionist research, in which the researcher was an active participant in finding solutions to the case organization’s problems, used the theory of diffusion to provide the necessary theoretical framework to conduct the study. The objective of this paper was to examine the extent of Six Sigma implementation and value creation for the organization and for customers.